Tranversus Abdominis Plane Block in Laparoscopic Surgery : Transversus Abdominis Plane Block in Laparoscopic Surgery - Hassan, Nazan; Ahmed , Iftikhar; Murtaza, Hina; Ali Malik, Aftab; Muhammad ch, Ihtasham; Shahid, Sosan; Mahmood, Shahid (Pakistan Journal of Health Sciences, 2022)
Good postoperative pain relief has been observed following various inguinal and abdominal procedures using transversus abdominis plane (TAP) block. Objective: To determine the outcome of laparoscopically assisted transverses abdominis plane block in laparoscopic cholecystectomy in comparison to periportal local anaesthesia in terms of mean pain. Methods: The study was conducted at the Department of General Surgery, Pakistan Atomic Energy Commission Hospital, Islamabad from January 2020 to June, 2020. In this randomized controlled trial, 92 patients underwent elective laparoscopic cholecystectomy were enrolled. Pain score was calculated by visual analogue score at 24 hours post-operatively. Data were entered in SPSS version 25.0. Comparison of both groups was done for pain score using t-test. Data were stratified. The t-test was performed. Results: Total 92 patients underwent elective laparoscopic cholecystectomy were selected foe the study. The subjects were divided into two categories such as Group1 or A (TAP block) and Group 2 or B (Periportal local anaesthesia). In the group A the 34(73.9%) subjects were males while the other 12(26.1%) were females, while in the group B the males were 31(67.4%) and 15(32.6%) were females. Mean VAS was 3.69±1.21 in group-A (TAP block) and 4.26±1.29 in group-B (periportal local anaesthesia) with p-value of 0.033. It is statistically significant. Conclusion: The one of the safest and effective modalities that provide postoperative analgesia with essentially decreased/ less postoperative pain when compared to periportal local anaesthesia is named as laparoscopic assisted TAP block.